HUBUNGAN ANTARA PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP MOTIVASI PENCEGAHAN KOMPLIKASI DIABETES MELITUS - Junita, Junita; Berti Anggraini, Rima; Meilando, Rizki (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Prevention of DM complications is very important, and patient motivation to maintain health plays a key role in disease management. Lack of knowledge about DM and its complications, as well as poor family support, can hinder effective prevention and management efforts. This study aims to determine the relationship between knowledge and family support on motivation to prevent complications of diabetes mellitus at Toboali Regional Hospital, South Bangka Regency in 2024. This study used a cross-sectional study design. This study was conducted by distributing questionnaires to 103 DM patients at Toboali Regional Hospital, South Bangka Regency on October 23 - November 18, 2024. The collected data were then analyzed univariately and bivariately using the chi-square test. The results of this study prove that there is a relationship between knowledge factors (p-value = 0.000) and family support (p-value = 0.000) on motivation to prevent complications of diabetes mellitus at Toboali Regional Hospital, South Bangka Regency in 2024. For hospitals, it is expected to form counseling services for patients and families in order to build better communication and increase emotional and practical support. This assistance can be carried out by nurses or health workers who are trained in providing motivation and diabetes management strategiesKeywords : Diabetes Mellitus, Family Support, Motivation, Knowledge.